Crisis Management: Chinese Entrepreneurs and Business Networks in Southeast Asia - EVERS, Hans-Dieter (Institutional Knowledge at Singapore Management University, 2000)
Examines crisis management among Chinese entrepreneurs and business networks in Southeast Asia based on an international conference held in Bonn, Germany. Includes the consideration of ethnic Chinese as key drivers of rapid economic growth in the region; Perception of the Chinese diasporic capital as a threat; Discourse on family-centered business networks.